The Improvement Of Safety Analysis Form (HIRARC) For Manual Tamping Works In Keretapi Tanah Melayu Berhad (KTMB): - - BIN SULKIFLI, MOHAMAD ARIF (Progress in Engineering Application and Technology, 2023)
Maintenance activities consist of routine servicing or heavy mechanicalmaintenance, such as tamping works[1]. These critical aspects must be completedproperly with full concentration and dedication by the workers who have beenassigned the task of maintaining the railway track to prevent injuries and accidents.In this study, the existing safety analysis form (HIRARC) of manual tamping worksin KTMB was improve to make sure to ensure it meets current needs. HIRARC is asystematic approach to identifying and controlling hazards in the workplace. It is avaluable tool for improving workplace safety and reducing the risk of accidents andinjurie. analysis and review for tamping manual works will be carried out to see thecurrent safety situation and to identify the hazards that exist when these works arecarried out. The level of risk will use risk assessment where likelihood and severitywill be used to get the risk level value. Results of the safety review, Improvementswill be made to the existing HIRARC form with the addition of resources of hazard.This enhancement will make the HIRARC form more detailed and easier to determinethe control measure to be used. The improved HIRARC will be brought to theinterview session for validation and review by KTMB track engineering staff.